The long freedom road; the civil rights story. - Harris, Janet (New York, McGraw-Hill, 1967)
A history of the civil rights movement, emphasizing the recent decade of problems and progress in integration, from the Supreme Court desegregation decision of 1954, to sit-ins, freedom rides, the march on Washington, voter registration, and Watts.
Bibliography: p. 147.
Keywords: African Americans -- Civil rights; African Americans -- Civil rights